2006
DOI: 10.1093/nar/gkl178
|View full text |Cite
|
Sign up to set email alerts
|

Structural stabilization of GTP-binding domains in circularly permuted GTPases: Implications for RNA binding

Abstract: GTP hydrolysis by GTPases requires crucial residues embedded in a conserved G-domain as sequence motifs G1–G5. However, in some of the recently identified GTPases, the motif order is circularly permuted. All possible circular permutations were identified after artificially permuting the classical GTPases and subjecting them to profile Hidden Markov Model searches. This revealed G4–G5–G1–G2–G3 as the only possible circular permutation that can exist in nature. It was also possible to recognize a structural rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 45 publications
(77 reference statements)
5
64
0
Order By: Relevance
“…Interestingly, an in silico analysis of other circularly permutated GTPases (Anand et al 2006) concluded that a consequence of repositioning the G3/switch II motif within the GTPase domain is that an anchoring carboxy-terminal domain is then required to fasten switch II and maintain its efficiency for GTP binding and hydrolysis. Our finding that the carboxy-terminal zinc-finger domain is necessary for the stability of YjeQ is consistent with this model.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an in silico analysis of other circularly permutated GTPases (Anand et al 2006) concluded that a consequence of repositioning the G3/switch II motif within the GTPase domain is that an anchoring carboxy-terminal domain is then required to fasten switch II and maintain its efficiency for GTP binding and hydrolysis. Our finding that the carboxy-terminal zinc-finger domain is necessary for the stability of YjeQ is consistent with this model.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis and secondary structure prediction of YqeH homologs revealed an N-terminal motif found in the treble clef family of zinc finger domains (24). The treble clef motif is contained within diverse proteins whose functions range from the binding of nucleic acids, proteins, and small molecules to the catalysis of phosphodiester bond hydrolysis (54).…”
Section: A Zinc Binding Motif In Gsyqehmentioning
confidence: 99%
“…G1-G5 are spatially close and are all associated with loop regions. G1-G4 are defined by conserved residues: G1 (GXXXXGK(S/T)), G2 (T), G3 (DXXG), G4 ((N/ T)KXD) (24,56). Interestingly, in YqeH, the G-regions of the CPG domain are rearranged as G4-G5-G1-G2-G3 in the linear sequence (Fig.…”
Section: The Crystallographic Structure Of Gsyqeh (Cpg and C-terminalmentioning
confidence: 99%
“…The 41 kDa protein possesses a central localized circular permuted GTPbinding domain with a G4-G1-G2-G3 motif (Leipe et al, 2002;Anand et al, 2006) and an N-terminal putative zinc finger domain with a conserved CXGCGX n CXRC motif . Interaction between the zinc finger domain and rRNA may be involved in the protein function (Anand et al, 2006). However, the C-terminus displays poor homology with proteins of known function, and is composed of nearly 20% of positively-charged amino acids, such as arginine, lysine and histidine.…”
Section: Introductionmentioning
confidence: 99%